2017
DOI: 10.1101/gr.222760.117
|View full text |Cite
|
Sign up to set email alerts
|

RNA editing in bacteria recodes multiple proteins and regulates an evolutionarily conserved toxin-antitoxin system

Abstract: Adenosine (A) to inosine (I) RNA editing is widespread in eukaryotes. In prokaryotes, however, A-to-I RNA editing was only reported to occur in tRNAs but not in protein-coding genes. By comparing DNA and RNA sequences of , we show for the first time that A-to-I editing occurs also in prokaryotic mRNAs and has the potential to affect the translated proteins and cell physiology. We found 15 novel A-to-I editing events, of which 12 occurred within known protein-coding genes where they always recode a tyrosine (TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(100 citation statements)
references
References 37 publications
5
93
0
Order By: Relevance
“…In E . coli , the tadA gene encoding tRNA-specific adenosine deaminase was responsible for bacterial tRNA and mRNA editing [ 18 ]. To investigate this possibility in Xoc , we constructed the tadA deletion and overexpressing strains, ΔtadA and tadA OE , respectively (see Methods).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In E . coli , the tadA gene encoding tRNA-specific adenosine deaminase was responsible for bacterial tRNA and mRNA editing [ 18 ]. To investigate this possibility in Xoc , we constructed the tadA deletion and overexpressing strains, ΔtadA and tadA OE , respectively (see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Bar-Yaacov and colleagues demonstrated that nonsynonymous A-to-I editing can occur in bacterial mRNA [ 18 ]. The authors found that A-to-I editing in hokB , which encodes a toxin that confers antibiotic tolerance, increases as a function of cell density and enhances toxicity of the protein [ 18 ]. Furthermore, tRNA-specific adenosine deaminase (TadA) was identified as the A-to-I editing enzyme in Escherichia coli , which expands the role of tadA as both a tRNA- and mRNA-editing enzyme in bacteria [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…1b). To facilitate this test, we generated a robust reporter by cloning the E.coli Hokb (ecHokb) gene containing tRNA-like CTACGAA sequence, which has been reported to be highly edited by ecTadA at RNA levels [14], into a CMV promoter-driven vector. Then, this reporter was co-transfected with a sgRNA targeting HEK site 3 and ABEmax or its mutated variants, and the A-to-G editing e ciencies in ecHokb cDNA (reversely transcribed from mRNA) or genomic DNA (gDNA) were determined by deep sequencing on ecHokb cDNA or gDNA amplicons.…”
Section: Engineering Abemax With Reduced Rna Deaminase Activitiesmentioning
confidence: 99%
“…Liu and colleagues [ 11 ] suggested that adenosine deaminases acting on tRNA (ADATs) may mediate mRNA editing in fungi, possibly together with specific cofactors. Indeed, ADATs were recently shown to catalyze the deamination of adenosines in both tRNA and mRNA in bacteria [ 18 ]. However, deletion of the F .…”
Section: Q3: How Is Rna Editing Catalyzed?mentioning
confidence: 99%
“…There, editing targets evolutionary conserved toxin—antitoxin pairs. Editing of the hokB toxin transcript increased toxicity and was conserved in the pathogenic bacteria Klebsiella pneumoniae and Yersinia enterocolitica [ 18 ], revealing another correlation of editing and pathogenicity.…”
Section: Q5: How Does Rna Editing Relate To Fungal Pathogenesis?mentioning
confidence: 99%